Presentations of gunshot injuries to the extremities in a tertiary hospital in Port Harcourt - Obene, Tonye Adiyi; Abhulimen, Victor (International Surgery Journal, 2022)
Background: There is an increasing incidence of gunshot injuries in most countries around the world. Causes of gunshot injuries include herdsmen assault on communities, religious and ethnic riots, student cultism, inter-tribal wars, accidental injuries at funeral ceremonies and politically motivated murder. This study aims to highlight the presentations of gunshot injuries to the extremities in Port Harcourt. Methods: This was a prospective carried out on all patients who presented with gunshot injuries to the extremities at the University of Port Harcourt Teaching Hospital during the period of the study. Data on age, gender, anatomical region of the body involved in the injury, nature of the gun used, time between injury and presentation at the hospital were obtained. The information gotten was analyzed and presented in form of tables and figures. Results: Eighty-two subjects with 106 injuries were evaluated. Mean age±SD=28.28±8.04 years. Seventy were males and 12 females (M:F=5.83). Most were unmarried and unemployed. Eighty nine percent presented to the hospital within 6 hours of injury. The AK 47 and locally made pistol were the most used weapons. The left extremity was more affected than the right. Conclusions: This study showed that young adult unemployed males suffered more gunshot wounds than females. Subjects presented early to the hospital. The AK 47 and the local pistol were the weapons mostly used in inflicting these injuries. Most injuries were sustained on the leg.